Use of the Minimally Invasive Reduction Instrumentation System for Facilitating Alignment and Reduction When Performing Minimally Invasive Plate Osteosynthesis in Three Dogs. (15th April 2018) - Townsend, Sarah; Lewis, Daniel D.
Abstract : The Minimally Invasive Reduction Instrumentation System (MIRIS) was utilized to facilitate minimally invasive plate osteosynthesis (MIPO) of distal limb diaphyseal comminuted fractures (2 crural, 1 antebrachial) in three dogs. The MIRIS facilitated efficient MIPO in all three fractures. Radial and tibial lengths were restored within 2% of the length of the intact bone and postoperative frontal and sagittal plane angulation were within 3° of the normal contralateral limb for each of the fractures. Fixation failed in one of the tibial fractures when the plates bent a week following surgery. The implants were removed and the fracture was restabilized via MIPO facilitated by the MIRIS. Inappropriate implant selection was considered the primary reason for implant failure. All three fractures achieved union by 10 weeks following surgery. The dog that underwent revision surgery developed a surgical site infection 5 months following revision surgery, which necessitated implant removal. All three dogs had excellent limb function at the time of the final evaluation. This system resulted in reductions that were near anatomic, with acceptable restoration of length and alignment and excellent limb function.